2009
DOI: 10.1093/bja/aep160
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the efficacy of convection warming in anaesthetized children

Abstract: (i) Although the effectiveness of this warming technique is influenced by patient/procedure characteristics, these do not predict normothermia (uncertainty +/-28 min). Effectiveness is independent of simple thermal measures. (ii) Previously described measures of vasoconstriction are not valid in children. (iii) Our model shows children's thermal properties change with their T(core). However, key factors are unknown for an individual and our model does not predict heating efficacy. (iv) To minimize the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Given the spread of ages and weights in our study, it might be anticipated that morphology should influence both heat gain and loss more than it did, particularly because, compared to adults, high cutaneous thermal losses have been observed in children under anesthesia (12). However, we observed the same outcome in a previous study on T core behavior during convection warming (21). In that study, we found standard morphological indices had an error of ±28 min in predicting time to regain lost heat.…”
supporting
confidence: 90%
“…Given the spread of ages and weights in our study, it might be anticipated that morphology should influence both heat gain and loss more than it did, particularly because, compared to adults, high cutaneous thermal losses have been observed in children under anesthesia (12). However, we observed the same outcome in a previous study on T core behavior during convection warming (21). In that study, we found standard morphological indices had an error of ±28 min in predicting time to regain lost heat.…”
supporting
confidence: 90%
“…The warmed children were heated by our previously described convective technique using a Bair Hugger set at 43°C (Bair Hugger; Arizant Healthcare Inc., Eden Prairie, MN, USA). This temperature was reduced as core temperature approached normothermia – although they remained convectively warmed.…”
Section: Methodsmentioning
confidence: 99%
“…Mean room RH was 52%. Descriptions of the accuracy of these measurements can be found in our prior publications . Data that were collected on various time periods, anthropometry, demographics, temperature, and RH are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations